Effect of intercropping cowpea on dry-matter and grain yield of millet in the semi-arid zone of Mali - Hulet, H.; Gosseye, P. (International Livestock Centre for Africa, 1986)
A study conducted to determine the effect of intercropping cowpea on dry-matter and grain yield of millet in the semi-arid zone of Mali. Presents and discusses physical and chemical characteristics at various depths of loamy sand soil, planting density and plant population, number of millet and cowpea hills per hactare, and millet and cowpea yield (Stems and leaves) over three consecutive years at Niono and Banamba.